Comparative Transcriptomic Analysis Reveals Divergent Stress Adaptation Strategies in Gamma-Induced Soybean Mutants - Gumus, Tamer; Meric, Sinan; Ayan, Alp; Ozden, Buse; Emlik, Simge; Celik, Ozge; Yilmaz, Alper; Atak, Cimen (MDPI, 2026)
Soybean (Glycine max L.) is an important agricultural crop for human food and animal feed. Soybean yield is severely constrained by abiotic stresses such as salinity and drought, which affect large proportions of arable and irrigated lands worldwide. This necessitates the development of new soybean varieties tolerant to these stress factors. Mutation breeding is an effective approach to improve the stress tolerance of plants due to increased genetic diversity. In this study, two gamma-induced salinity and drought-tolerant soybean mutants (SM1 and SM3-1) were compared with the parental line S04-05 using GO and KEGG pathway enrichment analyses. GO enrichment analyses revealed extensive differential gene expression in the mutant lines under stress conditions, with significant enrichment of pathways related to photosynthesis, hormone signaling, carbohydrate metabolism, and flavonoid and isoflavonoid biosynthesis. Genotype-specific analyses indicated that the SM3-1 mutant exhibited a dynamic regulatory response associated with maintaining the photosynthetic apparatus and chloroplast homeostasis under stress, whereas the SM1 mutant showed an adaptation strategy based on metabolite-mediated osmotic adjustment and ROS scavenging. Compared to the parental variety S04-05, the mutants showed distinct metabolic regulation in phenylpropanoid/isoflavone metabolism, with upregulation of many isoflavone biosynthesis genes under salinity, drought, and untreated conditions, indicating a key and sustained role of this pathway in stress tolerance. Most SNPs identified in the isoflavone biosynthesis pathway consist of moderate-impact and modifier variations. These findings suggest that gamma mutagenesis and subsequent selection processes allow for the development of novel genetic variants that operate through different physiological and metabolic mechanisms but exhibit similar levels of tolerance. In this respect, the study reveals that mutation breeding is a potentially sustainable and effective breeding strategy for increasing abiotic stress tolerance in soybeans.
Keywords: soybean; RNA-seq; isoflavonoid; salinity; drought; mutation breeding; SNP; PLANT-GROWTH; FLAVONOIDS; METABOLISM; Plant Sciences